Emma Lucy Braun's forest plots in eastern North America. Issue 2 (25th January 2018) - Ricklefs, Robert E.
Abstract: Relative abundances of tree species are presented for the 348 forest plots described in E. Lucy Braun's (1950) book, Deciduous Forests of Eastern North America (Hafner, New York, facsimile reprint 1972). Information about the plots includes forest type, location with latitude and longitude, WorldClim climate variables, and sources of original studies where applicable. No copyright restrictions are associated with the use of this data set. Please cite this article when the data are used in other publications.